Pengembangan Model Pembelajaran dalam Pelatihan Berbasis Lingkungan bagi Guru Madrasah Aliyah Program Ilmu Pengetahuan Sosial - Endang Sutisnowati (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[LEARNING MODEL DEVELOPMENT IN ENVIRONMENTAL-BASED TRAINING FOR TEACHERS OF SOCIAL SCIENCE PROGRAMS IN MADRASAH ALIYAH]. The fundamental problem in this research, is that learning in the Madrasah Aliyah Social Science program which starts from planning to evaluation has not been based on the environment or contextual, therefore this research uses a type of development research with development methods to produce certain products and test the effectiveness of the products being analyzed. qualitatively and qualitatively descriptive. The conclusion of this study resulted in two products, namely the development of a training learning model in the form of an environment-based training learning program design which was validated by experts, obtaining an average score of 94% and an environment-based learning guide with a blended learning pattern, an average score of 98%. The conclusion of the research stages of developing an environment-based training learning model, obtained an average score of 89.91% accompanied by environmental-based learning guide products obtained an average score of 88.25%, while the teacher's ability to prepare HOTS questions as an evaluation tool and is an integral part in this environment-based learning, the average score is 89.53%. Thus the product of this model development is very feasible to be a system product at the Education and Training Center for Technical Education and Religious Personnel.